Phosphorescent OLEDs with extremely low efficiency roll-off enabled via rationally designed benzimidazole-based bipolar hosts. (September 2020) - Zhang, Tian; Miao, Jingsheng; Ali, Muhammad Umair; Shi, Ming; He, Yaowu; Fu, Tianchen; Meng, Hong
Abstract: Phosphorescent organic light-emitting diodes (PhOLEDs) have manifested enormous potential for display and lighting applications because of their high internal and external quantum efficiencies, nevertheless, severe efficiency roll-off at high luminance remains a major bottleneck in their large-scale commercialization. Herein, two new bipolar host compounds, DCbz-Ph-Bz and DDPA-Ph-Bz, based on carbazole/diphenylamine as the donor and benzimidazole as the acceptor, are successfully obtained. By employing these materials as hosts, extremely low efficiency roll-off PhOLEDs without sacrificing the efficiency are realized. Especially, green PhOLED based on DDPA-Ph-Bz as the host and GD001 as the dopant demonstrated a low turn-on voltage of 2.6 V, a peak current efficiency (CE) of 62.2 cd/A and a maximum luminance of 39, 370 cd/m 2 . Importantly, our green device exhibited a very low efficiency roll-off as the peak external quantum efficiency (EQE) of 18.3% at 1000 cd/m 2 was still retained at 17.6% even at a high luminance of 10, 000 cd/m 2 . Likewise, red PhOLED with DCbz-Ph-Bz as the host and RD001 as the dopant displayed a high maximum EQE of 20.1% and a CE of 24.5 cd/A. High efficiency with low efficiency roll-off in our devices reveals the potential of bipolar molecules as excellent hosts to achieve high-performance PhOLEDs. Graphical abstract: Image 1 Highlights: Two new bipolar host materials are synthesized that demonstrate exceptional thermal stability and high triplet energies. Red PhOLEDs containing our newly developed compound as host manifested an impressive EQE of 20.1%. Green PhOLEDs showed an EQE of 18.3% at 1000 cd/m 2, that was retained at 17.6% even at a very high luminance of 10, 000 cd/m 2 .